HUBUNGAN KARAKTERISTIK INDIVIDU DENGAN PERILAKU KEAMANAN PANGAN PENJAMAH MAKANAN DI KANTIN UNIVERSITAS GADJAH MADA - , EMA NURTIKA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Realizing customer satisfaction is a defense strategy required in enhancing food business competitiveness. Level of customer satisfaction depends on the quality of product that is offered. One factor relates to food quality is the food safety assurance. The outbreak of Hepatitis A in 2008 amon GMU students triggered awareness in food service practice at university canteens. Therefore, food handlers play important role in food safety assurance. Food handlersâs behaviour might be determined by individual characteristics. Objective : To identify the association between individual charcateristics with behaviour (knowledge, attitude, and practice) of food safety among food handlers in canteen of Gadjah Mada University. Instruments and Methods : Subjects were food handlers who work in canteens within UGM, which then categorized into 3 clusters based on the discipline of faculties in which the canteen located, i.e. Agro-Health, Science-Technology, and Sosio Humaniora clusters. Data of individual characteristics, knowledge, and attitude of food handlers were obtained through self administered questionnaire while data of food handlersâ practice were collected by using observational check list. Form of food safety score was used to evaluate the overall quality of foods. Statistical analysis were performed by using Chi Square test, Spreaman correlation and One way ANOVA analysis. Result : There was no significant relationship between individual characteristic and food handlerâs behaviour on food safety (p>0,05). However, there was a positive correlation between knowledge and attitude and both attitude and behaviour (p<0,05). Differences of food safety behaviour were found in cluster Agro-Kesehatan, Sains-Teknologi and Sosio Humaniora. Overall, the quality of foods in canteen classified as susceptible but it still safe to consume. Conclusion : Individual characteristics (age, gender, education level, professional experience, and job training) is not associate significantly with behaviour (knowledge, attitude and practice) of food safety among food handlers in canteen of Gadjah Mada University.